The relationship between peer relations and depression among adolescents in Selangor, Malaysia - Uba, Ikechukwu; Yaacob, Siti Nor; Juhari, Rumaya (eurojournals, 2009)
The current study examined the predictors of depression in peer relationship (bullying, victimization and pro-social behaviour), using 242 teenage sample aged between 13-17 years (mean age = 14.67 years; std.dev = 1.27). The Children Depression Inventory (CDI) (Kovac, 1985) was used to measure adolescent depression. The Peer Relationship Questionnaire (PRQ) by Rigley and Slee (1993) was used to assess bullying, victimization and pro-social behaviour among respondents of the study. The study indicated that depression has a significant and positive correlation with both bullying (r = .296, p ≤.01) and victimization (r = .432, p ≤ .01) and a negative and non- significant correlation (r = - .101, p > .05) with pro-social behaviour. Significant difference (t = 3.306, p ≤ .05) was only found between male and female teenagers in bullying. The survey further discovered victimization as the unique predictor of depression (Beta = .373, p ≤.0001) among peers. The results of the study provide confirmation of earlier findings on peer relationship. Recommendations of the study centre on the need to expand beyond the self report of internalizing and externalizing depression reported by the teenage respondents of the study.